Vehicular ad hoc network and clustering routing algorithm applied in wilderness scenarios - Mohsen MOHAMED; Kai-kai XU; Wei-wei XIA; Yi WU; Lian-feng SHEN (Tongxin xuebao)
To solve the communication problem among vehicles in wilderness scenarios such as desert and Gobi or between the vehicles and the outside,a special architecture of VANET was proposed and its clustering and routing algorithm was analyzed.Based on different types of communication terminals each vehicle equips and the location,speed and driving direction information of the periodic message,the vehicles are organized into different clusters.The head of each cluster chooses the best route for its members when they ask for inner-clustering communications or inter-clustering communications.It also searches the nearest vehicle which equips satellite communication terminals or land mobile communications terminals to forward messages when a member requests communicating with the outside of the network.Simulation results show that the proposed algorithm has higher network stability,higher data delivery ratio and less routing overhead.